Sosialisasi Cerdas Menabung: Upaya Peningkatan Literasi Keuangan di Kalangan Remaja Sanggar Bimbingan Rawang - Ariyanto, Ahmad; Firdaus, Firdaus; Nurhayati, Nurhayati; Noegroho, Andro Dewantara (Society : Jurnal Pengabdian Masyarakat, 2025)
This study aims to enhance the understanding of the importance of saving among students of Sanggar Bimbingan Rawang through educational and training approaches. This research employs a qualitative design with a case study approach, involving 25 students from grades Three to Six. Primary data were collected through semi-structured interviews and documentation to evaluate the students' initial understanding of financial management and behavioral changes after the program. The training program was conducted in several sessions, encompassing both theory and practice, including demonstrations and simulations of saving management. Evaluation was conducted by analyzing qualitative data using thematic analysis techniques to obtain comprehensive conclusions. It is expected that this program will provide significant benefits for the financial development of students in the future and emphasize the importance of collaboration between educational managers and the community.